2019
DOI: 10.1021/acs.jmedchem.9b00059
|View full text |Cite
|
Sign up to set email alerts
|

Modification and Biological Evaluation of a Series of 1,5-Diaryl-1,2,4-triazole Compounds as Novel Agents against Pancreatic Cancer Metastasis through Targeting Myoferlin

Abstract: Pancreatic cancer is one of the most common cancers with an extremely low survival rate. Metastasis, as one of the key reasons of cancer-related death, is found in more than 50% pancreatic cancer patients at diagnosis. Novel therapeutic targets and drugs blocking cancer metastasis are urgently needed. Herein, we report a series of 1,5-diaryl-1,2,4-triazole derivatives as potent antimetastatic agents. Lead compound 6y displayed effective antimetastatic activities in pancreatic cancer in vitro and in vivo. Conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Targeting myoferlin at the expression or functional levels remains, however, the next challenge. Interestingly, recent studies identified new small compounds interacting with the myoferlin C2D domain and demonstrating promising anti-tumoral/metastasis properties in breast and pancreas cancer [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting myoferlin at the expression or functional levels remains, however, the next challenge. Interestingly, recent studies identified new small compounds interacting with the myoferlin C2D domain and demonstrating promising anti-tumoral/metastasis properties in breast and pancreas cancer [133,134].…”
Section: Discussionmentioning
confidence: 99%
“…This molecule can reverse EMT of breast cancer and decrease pulmonary metastasis [63]. Another diaryl-1,2,4-triazole derived compound targeting MYOF also demonstrates potent antitumor effects similar to that of MYOF depletion [64]. Such MYOF-targeting compounds are expected to yield promising therapeutic benefits in the treatment of cancer.…”
Section: Role Of Myof In Cancermentioning
confidence: 99%
“…The anticancer activity of 6y is positively associated with the expression of myoferlin, and 6y is insensitive to myoferlin depletion. The specific mechanisms may be mediated by blocking the receptor tyrosine kinases, inhibiting the secretions of matrix metalloproteinase and reversing the EMT process . Overall, myoferlin may provide a novel therapeutic target in PAC.…”
Section: Roles Of Myoferlin In Cancersmentioning
confidence: 99%
“…39 The specific mechanisms may be mediated by blocking the receptor tyrosine kinases, inhibiting the secretions of matrix metalloproteinase and reversing the EMT process. 69 Overall, myoferlin may provide a novel therapeutic target in PAC.…”
Section: Myoferlin In Pancreatic Adenocarcinomamentioning
confidence: 99%